Pregnenolone effects on provoked alcohol craving, anxiety, HPA axis, and autonomic arousal in individuals with alcohol use disorder - Milivojevic, Verica; Sullivan, Liam; Tiber, Jessica; Fogelman, Nia; Simpson, Christine; Hermes, Gretchen; Sinha, Rajita (Psychopharmacology, 2023)
Rationale Chronic alcohol intake down-regulates GABAergic transmission and reduces levels of neuroactive steroids. These changes are associated with greater stress dysregulation and high alcohol craving which in turn increases relapse risk. Objectives This study tested whether potentiation of the neurosteroid system with pregnenolone (PREG), a precursor to neuroactive steroids and known to increase GABAergic transmission, will normalize chronic alcohol-related stress adaptations in the hypothalamic–pituitary–adrenal (HPA) axis and autonomic responses and reduce alcohol craving to significantly impact relapse risk. Methods Forty-three treatment-seeking individuals with alcohol use disorder (AUD) were randomized to placebo (PBO) or supraphysiologic pregnenolone doses of 300 mg or 500 mg treatment using a parallel-between subject design as part of a larger 8-week pilot clinical trial. In week 2, they participated in a 3-day laboratory experiment where on each day they self-administered the assigned study drug in the laboratory and were then exposed to 5-min personalized guided imagery provocation of stress, alcohol, or neutral/relaxing cues, one condition per day on separate days, in a random, counterbalanced order. Repeated assessments of alcohol craving, anxiety, HPA axis, heart rate (HR), systolic (SBP), and diastolic blood pressure (DBP) and serum pregnenolone levels were made on each day. Results Pregnenolone levels were significantly increased in the PREG groups versus PBO. PREG treatment decreased stress- and alcohol cue- induced craving and dose-specifically reduced stress-induced anxiety in the 300 mg/day group. Both PREG doses compared to PBO also normalized CORT/ACTH and increased stress-induced HR, stress- and cue-induced SBP, and in the 300 mg PREG group cue-induced DBP responses relative to neutral condition. Conclusions Findings indicate that pregnenolone decreases stress- and alcohol cue-provoked craving and normalizes HPA axis and autonomic arousal in individuals with AUD, thereby supporting the need for further assessment of pregnenolone in the treatment of AUD.